Protective Effect of Cyclically Pressurized Solid–Liquid Extraction Polyphenols from Cagnulari Grape Pomace on Oxidative Endothelial Cell Death - Anna Posadino (18090520) (2018)
The aim of this work is the evaluation of a green extraction technology to exploit winery waste byproducts. Specifically, a solid–liquid extraction technology (Naviglio Extractor®) was used to obtain polyphenolic antioxidants from the Cagnulari grape marc. The extract was then chemically characterized by spectrophotometric analysis, high-performance liquid chromatography, and mass spectrometry, revealing a total polyphenol content of 4.00 g/L ± 0.05, and the presence of anthocyanins, one of the most representative groups among the total polyphenols in grapes. To investigate potential biological activities of the extract, its ability to counteract hydrogen peroxide-induced oxidative stress and cell death was assessed in primary human endothelial cells. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test, used to assess potential extract cytotoxicity, failed to show any deleterious effect on cultured cells. Fluorescence measurements, attained with the intracellular reactive oxygen species (ROS) probe 2′,7′-dichlorodihydrofluorescein diacetate (H2DCF-DA), revealed a strong antioxidant potential of the marc extract on the used cells, as indicated by the inhibition of the hydrogen peroxide-induced ROS generation and the counteraction of the oxidative-induced cell death. Our results indicate the Naviglio extraction, as a green technology process, can be used to exploit wine waste to obtain antioxidants which can be used to produce enriched foods and nutraceuticals high in antioxidants. Other Information Published in: Molecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/molecules23092105